EFFECTS OF X-RAY RADIATION EXPOSURE ON SPERM MOTILITY AND MORPHOLOGY CHANGES OF WISTAR STRAIN RATS - Hariyoto, Bangun Oktavian; Soebadi, Doddy M; Soetojo, Soetojo; Soeprijanto, Bambang (Indonesian Urological Association, 2020)
Objective: To analyze the differences of sperm motility and viability changes in Wistar Rats that exposed to X-ray radiation compared to Wistar Rats that were not exposed to X-ray radiation. Material and Methods: Experimental laboratory research within vivo design using Wistar strain rats as subjects. There are three treatment groups in this study: rats exposed to 50 mGy X-ray radiation, 100 mGy, and 200 mGy and one untreated control group. Radiation exposure was calibrated using the RTI Piranha dosimetry. After radiation exposure, at week 4, orchidectomy was performed in rats. Sperm analysis was carried out to determine sperm motility by direct observation and sperm viability by Hematoxylin Eosin (HE) staining observations using a light microscope. One Way ANOVA was used to compare motility and viability of rats spermatozoa in the treatment group compared to control group with a significant value of p<0.05. The analysis was continued with a Post Hoc test to determine the differences in each group. Results: The percentage of motile sperm decreased in all treatment groups compared to control group (p<0.05). There was no significant difference in mean sperm motility on rats exposed to 200 mGy X-ray radiation compared to 100 mGy X-ray radiation (p>0.05). Viability counts decreased in all treatment groups compared to control group (p<0.05) and the spermatozoa viability in 200 mGy radiation group was not significantly different from 100 mGy group (p>0.05). Conclusion: X-ray radiation exposure decreases sperm motility and viability in Wistar rats with the optimum doses 100 mGy.